Transcriptome analysis of lncRNA expression patterns in human congenital lung malformations - Weili Yang (BMC, 2021)
Abstract Objectives To explore the long non-coding RNA (lncRNA) expression pattern of congenital lung malformations on a genome-wide scale and investigate their potential biological function in four subtypes of congenital lung malformations. Methods We obtained both lesions and normal lung control tissues from the patients diagnosed with CPAM-I, CPAM-II, ILS, and ILS-CPAM, and underwent lobectomy (i.e., surgical removal of the whole lobe which contains the localized lesion as well as normal lung tissue). Then, we performed lncRNA transcriptome profiling in these tissues by RNA sequencing (RNA-seq). A comprehensive bioinformatics analysis was conducted to characterize the expression profiles and relevant biological functions and for multiple comparisons of lncRNA expression in the different subtypes of congenital lung malformation tissues. Furthermore, the lncRNA-mRNA co-expression network was constructed, and dysregulated mRNAs were functionally analyzed. Finally, gene set enrichment analysis (GSEA) was used to predict the potential molecular mechanism of the identified lncRNAs. Results A total of 5921 lncRNA transcripts were identified between congenital lung malformations tissues and normal lung control tissues. Compared with normal lung control, 481of these expressed lncRNAs were upregulated and 142 were downregulated in CPAM-I, 91 were upregulated and 14 were downregulated in CPAM-II, 39 were upregulated and 38 were downregulated in ILS, and 201 were upregulated and 38 were downregulated in ILS-CPAM. Unsupervised clustering and principal component analysis of the expressed lncRNAs visualized the differences between normal lung control and different subtypes of congenital lung malformations samples. We also confirmed significant differences in the composition of differentially expressed genes (DEGs) and the differentially expressed lncRNAs (DE lncRNAs) between CPAM-I and other subtypes of congenital lung malformations, as well as in normal lung control tissues, and observed enrichment of DEGs in the regulation of the immune system, cell projection organization, and inflammatory pathways. Finally, we identified the lncRNA FLJ26850 might be related to congenital lung malformations via ZNF473. Conclusions Significant differences in lncRNAs expression patterns were observed between different subtypes of congenital lung malformations and normal control. The lncRNA FLJ26850 might be related to congenital lung malformations via ZNF473.